International cooperation - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1980)
The progress achieved by CIAT's cassava program through training activities related to the crop in Latin America, Asia, and Oceania are given. In collaboration with the training office at the Centro Internacional de Agricultura Tropical, the cassava program in 1980 trained 38 professionals from 15 countries (Brazil, Colombia, Mexico, Bolivia, USA, Thailand, Dominican Republic, S. Africa, Ecuador, Haiti, Honduras, W. Germany, the Netherlands, Great Britain, and Italy). (CIAT)